Pembuatan Perencanaan Desain Gambar Bangunan Gapura Desa Kandawati Dan Pendopo Makam Kandawati - Rayhan, Ahmad; Maulana, Hanif (Sinesia : Jurnal Pengabdian Masyarakat, 2024)
A gate is a structure in the form of an entrance or gate to an area or area. This structure is often found in temples and other Hindu religious shrines, because the gate is an important element in Hindu architecture. Gapura is also often interpreted as a gate. Pendopo is a building without walls with many pillars or pillars, this building is used as a place for meetings, pilgrimages, community meetings, and so on. Along with the progress of Kandawati village, especially the progress of Religious Tourism, it is necessary to build a gate as an icon of Kandawati Village. This gate building serves as an icon to attract tourists who will visit Kandawati Village. Therefore, the purpose of this service is to plan the design of the gate and pavilion of the Gandawati tomb in accordance with the cultural characteristics of Kandawati Village. The method of implementing the service includes site surveys, making working drawings of gates and pavilions, making budget plans, exposing the results of drawing designs and costs to the village. The result of this service is the compilation of technical drawings and budget plans that can be used by the village as the basis for the gate and pavilion construction plan. In this way, the village will be equipped with plans and cost plans when construction work is carried out.